An ever-expanding story of cyst formation - Gallagher, Anna Rachel; Obermüller, Nicholas; Cedzich, Anna; Gretz, Norbert; Witzgall, Ralph (Cell & tissue research, 2000)
Autosomal-dominant polycystic kidney disease represents one of the most common monogenetic human disorders. The cloning of the PKD1 and PKD2 genes, which are mutated in far more than 90% of the patients affected by this disease, has generated high hopes for a quick understanding of the pathogenesis of cyst formation. However, these expectations have not yet been fulfilled, since the function of both polycystin-1 and polycystin-2, the two proteins encoded by PKD1 and PKD2, still remains a puzzle. In this review, we will highlight some of the characteristics of polycystic kidney disease, briefly touch on polycystin-1, and then go on to describe recent results of experiments with polycystin-2, since the latter is the major focus of our work. We will discuss new evidence which suggests that autosomal-dominant polycystic kidney disease actually behaves recessively on a cellular level. Finally, a model will be presented that tries to explain the available data.
Gesehen am 28.06.2022